Nueva propuesta interiorista del Banco Nacional de Fomento de la ciudad de Machala - Sánchez Castillo, Daniela Olinda (2015)
The National Bank of Development is a governmental establishment that serves to support small and medium producers in order to create jobs, it is worth mentioning that banks in Machala city have not functional buildings that allow them to provide quality service towards users, and a comfortable workspace for their employees; the National Bank of Development is not an exception, it was founded in 1964, and its current situation indicates poor conditions and a constant deterioration; including the particularity of it does not have a ventilation system that supplies efficiently; each of its renovations were done without structural criteria; and, in the historical archives, there is not evidence about documentation regarding the evolution of this building. For these reasons, this research is based on developing a New Interior Design. Proposal of the National Bank of Development in Machala city, which enables it to provide better service through innovation and spatial design, based on a concept that offers identity, ergonomics and functionality.